Evaluation of the Patients with Placenta Praevia in Mymensingh Medical College Hospital, Bangladesh - Sharmin, Tahmina; Hasan, Mohammad Rajibul; Mirza, Tayeeba Tanzin; Shamsi, Sanjida; Panna, Laila Kamrunzzahan (Community Based Medical Journal, 2024)
Placenta praevia is a life-threatening condition both for mother and foetus and defines high risk pregnancy. A cross-sectional, observational study was conducted from July to December of 2021 in the Department of Obstetrics & Gynaecology of Mymensingh Medical College Hospital, Mymensingh, Bangladesh, to assess the relationship between previous Caesarean scar and subsequent development of placenta praevia. A total of 48 women of placenta parevia were taken in this study as diagnosed through ultrasonogram. In age distribution of these patients, peak incidence was found in the 26-35 years age group (54.10%) and the oldest was at her 42 years. Most of the patients (35.41%) did not take any antenatal check-up before their admission into hospital. The majority patients (64.58%) had history of previous Caesarean scar than vaginal delivery (35.41%) and previous two scars (51.61%) were most common. Ultrasonographically, partial variety was more (29.10%) common than others. Most pregnancies were (78.08%) delivered abdominally. In fetal outcome, 22.91% of babies were premature but did not need any NICU support, whereas 22.83% needed admission into NICU. Primary postpartum haemorrhage was the most common among complications (37.50%). This study suggests identifying the risk factors for placenta praevia. Early diagnosis, creating awareness and organizing a strong supportive surgical skilled team are needed to reduce maternal and foetal morbidity and mortality in such cases. CBMJ 2024 July: vol. 13 no. 02 P: 135-140